Deflazacort: desenvolvimento e validação de metodologia de análise e estudos de dissolução de comprimidos e cápsulas manipuladas - Corrêa, Giane Márcia (2006)
In this work the validation end development methodologies for determination the deflazacort glicocorticoid in tablets and capsules.The methods used for determination for delazacort were: liquid chromatography (LC), ultraviolet spectrophotometry (UV) and visible spectrophotometry. The CLAE was operated at controlled-ambient temperature with reverse fase C18 , using a mobile phase composed of acetonitrile and wather (80;20 V/V), detector at 240 nm. In the UV spectrophotometry method applied as solvent ethanol and detection at 244 nm. Another used method was visible spectrophotometry applied as solvent and reagent blue the tetrazolio at 0,5% methanol and hidroxid tetrametilamonio at 10% in methanol and as solvent ethanol. The detection at 519 nm. The proposed method showed good linearity, precison and accuracy. Moreover, a method for the dissolution of deflazacort in solid dosage formulations was developed and validated. Studies were conducted by basket and paddle methods at in 900 mL 0,1N hydrochloric acid at 50 rpm and quantification was achieved by UV spectrophotometry. The validation showed good specificity, linearity, precison and accuracy.